2006
DOI: 10.1038/sj.sc.3101899
|View full text |Cite
|
Sign up to set email alerts
|

Leisure satisfaction and psychiatric morbidity among informal carers of people with spinal cord injury

Abstract: Study design: Cross sectional survey. Objective: To examine the nature and prevalence of common mental disorders among informal carers of people with Spinal Cord Injury (SCI) and the association with their leisure satisfaction. Setting: Christian Medical College, Vellore, Tamilnadu, India. Methods: A cross-sectional survey of informal carers of people SCI at the Department of Physical Medicine and Rehabilitation. Fifty-three informal carers of people with SCI were interviewed using the Revised Clinical Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
2
22
4
Order By: Relevance
“…Contrary to previous research on caregiving among adults with SCI 5,6 and among youth with spina bifida 2 , caregiver education, marital status and current child age were not associated with caregiver psychological outcomes. It could be that for parents of youth with SCI, past education is not as important as current education/resources related to their child's injury, and marital status may not be as important as having other types of social support.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Contrary to previous research on caregiving among adults with SCI 5,6 and among youth with spina bifida 2 , caregiver education, marital status and current child age were not associated with caregiver psychological outcomes. It could be that for parents of youth with SCI, past education is not as important as current education/resources related to their child's injury, and marital status may not be as important as having other types of social support.…”
Section: Discussioncontrasting
confidence: 54%
“…1,2 Similarly, caregivers of adults with SCI report experiencing a low quality of life, 3,4 burden 5 and psychological distress. 6 Factors associated with poorer caregiver outcomes include less education, 6 not having a partner, 2 being female, 5,6 having a child of older age 2 and caring for a person/child with behavioral/ emotional problems. 2 The impact of injury severity and injury duration is unclear, as some researchers 5 have found that these factors predict poor caregiver outcomes, whereas others 6 have found no such relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver burden was not influenced by the gender (z ¼ À0. 13 Functional abilities of the care recipients Analysis of BI scores is listed in Table 3. Majority of the care recipients (n ¼ 27) had moderate-to-very severe disability.…”
Section: Assessment Of Caregiver Burdenmentioning
confidence: 99%
“…13 The family caregivers who willingly accept the role of caregiving may also experience certain level of distress and burden when they realize they have little support once they have taken over the role. 1,12 The purpose of this study was to determine the psychological impact and examine the burden of caregiving for caregivers of persons with SCI living in Fiji.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiving for an individual with SCI has been found to be exceedingly time consuming, stressful, and associated with deleterious effects on mental health and overall quality of life for the caregiver (Blanes, Carmagnani, & Ferreira, 2007;Boschen, Tonack, & Gargaro, 2005;Chen & Boore, 2008;Raj, Manigandan, & Jacob, 2006;Shewchuk, Richards, & Elliott, 1998). In a cross sectional study conducted in Brazil, it was found that SCI caregivers reported lower overall health-related quality of life and greater burden (Blanes et al, 2007).…”
Section: Introductiónmentioning
confidence: 99%